The influence of the human factor in the creation of aircraft engines - Виктория Викторовна Кокотина; Лариса Анатольевна Лесная; Виталий Григорьевич Харченко (Авіаційно-космічна техніка та технологія, 2021)
Ensuring the safety of the civil aviation system is the main goal of the International Civil Aviation Organization (ICAO) activities and the "human factor" was define as a priority in the field of flight safety. Given the variety of factors potentially affecting human performance, it is not surprising, that human error has been recognized as a major causative factor in virtually all air crashes and accidents since the inception of aviation. The reliability and safety of flights are influenced by: the quality of preparation of aviation equipment for flight, the quality of manufacture, assembly, acceptance, and pre-flight tests, the quality of design of aircraft and engines. The quality of workmanship is confirmed by the execution of control at each stage of manufacture. In any activity, the "human factor" is manifested by mistakes, oversights, and omissions, or miscalculations that a person makes when doing his job under certain conditions. The theory of the occurrence and prevention of errors associated with human physiology and the environment were described by H. Heinrich's "domino theory". Human errors form sequences in which the first error causes a chain of subsequent ones, keeping one of the dominoes standing behind each other, it is possible to prevent the consequences of an accident in the form of material damage or an accident. Human physiological features such as vision can be one of the dominoes and lead to erroneous actions. In the modern world, non-destructive testing methods are relevant and the role of a defectoscopistꞌs in determining the nature of a defect is quite large. Regular monitoring of vision (prophylactic examination) allows you to identify potential vision problems with a specialist, which can lead to erroneous actions. Human factors research is fundamental to understanding the context in which normal, healthy, skilled, well-equipped and reasonably motivated personnel make mistakes, some of which are fatal and, if the causes of human error are correctly understood, it will be possible to develop more effective prevention strategies errors, their control, and safe elimination.